2018
DOI: 10.1177/1942775118819679
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence and Reciprocity: Partnership Ethos at the University of Denver

Abstract: Research indicates that preparation programs featuring partnerships between universities and districts have a greater impact on career advancement of graduates than more conventional university-based programs. The University of Denver's (DU) Ritchie Program for School Leaders has been identified as a "model" of universitydistrict collaboration. This partnership program between DU and Denver Public Schools to develop transformative and courageous leaders launched a partnership ethos that defines the Educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Although governed by state licensure and national mandates, district-university partnerships are typically situated at different levels of the education system with their own structures of power and authority (Woulfin & Kruse, 2018). The work of partnerships in the field is typically characterized by the expertise of the partners and their natural predilection to frame problems and seek solutions in collaboration with one another (Elmore, 2004;Korach et al, 2019). Leithwood et al (2020) further warrant the importance of sustaining collaborative relationships in preparing aspiring candidates for the contextually specific demands of the principalship.…”
Section: Challenges In Maintaining and Sustaining A Partnershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Although governed by state licensure and national mandates, district-university partnerships are typically situated at different levels of the education system with their own structures of power and authority (Woulfin & Kruse, 2018). The work of partnerships in the field is typically characterized by the expertise of the partners and their natural predilection to frame problems and seek solutions in collaboration with one another (Elmore, 2004;Korach et al, 2019). Leithwood et al (2020) further warrant the importance of sustaining collaborative relationships in preparing aspiring candidates for the contextually specific demands of the principalship.…”
Section: Challenges In Maintaining and Sustaining A Partnershipmentioning
confidence: 99%
“…Data were analyzed to derive themes, their implications, and lessons learned. Data analysis involved coding of themes (e.g., Creswell & Poth, 2017) using deductive codes derived from the research questions and the literature from existing district-university partnerships (e.g., Korach et al, 2019;Sanzo, 2014) and inductive codes arising from transcript analysis, as checked for agreement among the raters. For example, the deductive coding related to how district-university partnerships can be sustained over time, why they survive, and how the preparation of qualified principals can happen on a large scale.…”
Section: Data Sources and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Orr and Barber's (2007) study showed that urban and rural programs implementing university-district partnerships had both greater preprogram and postprogram levels of commitment. These findings are further reinforced by Korach et al (2019) who argue that university-district partnerships form a "shared vision of preparing leaders to disrupt the status quo and the authority to create the structures and systems to support [this] vision . .…”
Section: Leadership Preparationmentioning
confidence: 99%
“….” (p. 46). By coconstructing, leadership districts share current practice and build contextual understanding while universities ensure “theoretical and conceptual anchors” to promote critical thinking (Korach et al, 2019, p. 2). Finally, Cosner et al (2015) demonstrate that, over time, a quality leadership pipeline can be built by providing a uniquely prepared workforce.…”
Section: Conceptual Frameworkmentioning
confidence: 99%